SLEEP QUALITY AND ASSOCIATED FACTORS OF SLEEP DISORDERS AMONG HEALTH SCIENCES STUDENTS AT DAI NAM UNIVERSITY IN 2023 (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the status of sleep disorders and identify associated factors among health sciences students at Dai Nam University in 2023.Subjects and methods: A cross-sectional descriptive study was conducted among 447 health sciences students majoring in Medicine, Nursing, and Pharmacy at Dai Nam University. Sleep disorders were assessed using the 5-item Athens Insomnia Scale (AIS-5). Students with an AIS-5 score > 4 were classified as having a sleep disorder. Data were analyzed using descriptive statistics, Chi-square tests, and multivariable logistic regression.Results: The prevalence of sleep disorders among students was 27.96%. The mean total AIS-5 score was 2.81 ± 2.83, ranging from 0 to 14 points. Among the AIS-5 components, the highest mean scores were observed for total sleep duration and overall sleep quality. After adjustment, academic major and year of study were significantly associated with sleep disorders. Nursing and Pharmacy students were less likely to have sleep disorders than Medicine students, while second-year students were more likely to have sleep disorders than first-year students.Conclusion: Sleep disorders are an issue of concern among health sciences students, particularly among Medicine students and second-year students.
Keywords: Sleep disorders, students, health sciences, AIS-5, Dai Nam University